Microbe-Mediated Biosynthesis of Nanoparticles: Applications and Future Prospects - Bhupendra Koul; Anil Kumar Poonia; Dhananjay Yadav; Jun-O Jin (Biomolecules, 2021)
Nanotechnology is the science of nano-sized particles/structures (~100 nm) having a high surface-to-volume ratio that can modulate the physical, chemical and biological properties of the chemical compositions. In last few decades, nanoscience has attracted the attention of the scientific community worldwide due to its potential uses in the pharmacy, medical diagnostics and disease treatment, energy, electronics, agriculture, chemical and space industries. The properties of nanoparticles (NPs) are size and shape dependent. These characteristic features of nanoparticles can be explored for various other applications such as computer transistors, chemical sensors, electrometers, memory schemes, reusable catalysts, biosensing, antimicrobial activity, nanocomposites, medical imaging, tumor detection and drug delivery. Therefore, synthesizing nanoparticles of desired size, structure, monodispersity and morphology is crucial for the aforementioned applications. Recent advancements in nanotechnology aim at the synthesis of nanoparticles/materials using reliable, innoxious and novel ecofriendly techniques. In contrast to the traditional methods, the biosynthesis of nanoparticles of a desired nature and structure using the microbial machinery is not only quicker and safer but more environmentally friendly. Various microbes, including bacteria, actinobacteria, fungi, yeast, microalgae and viruses, have recently been explored for the synthesis of metal, metal oxide and other important NPs through intracellular and extracellular processes. Some bacteria and microalgae possess specific potential to fabricate distinctive nanomaterials such as exopolysaccharides, nanocellulose, nanoplates and nanowires. Moreover, their ability to synthesize nanoparticles can be enhanced using genetic engineering approaches. Thus, the use of microorganisms for synthesis of nanoparticles is unique and has a promising future. The present review provides explicit information on different strategies for the synthesis of nanoparticles using microbial cells; their applications in bioremediation, agriculture, medicine and diagnostics; and their future prospects.